Negotiating Global Media in Conservative Contexts: Yaoi and Yuri Consumption Among Malaysian University Students - Rokiah, Paee; Roslina, Mamat; Roswati, Abdul Rashid (Penerbit UKM (UKM Press), 2025)
This study explores the consumption of Yaoi (boys’ love) and Yuri (girls’ love) media among Malaysian university students, focusing on three objectives: identifying demographic characteristics and consumption patterns, exploring motivations for engagement, and examining reasons for discontinuation alongside socio-cultural perceptions. Based on a survey of 111 students from five Malaysian universities, the findings reveal the significant appeal of Yaoi and Yuri genres through their emotional depth, compelling storytelling, and alternative relationship narratives. Female respondents dominated the sample (84%), with a strong preference for non-explicit narratives such as Shonen-ai and Shoujo-ai, reflecting the conservative cultural context of Malaysia. Respondents highlighted motivations such as emotional engagement (54.2%), intricate storylines (52.8%), and aesthetic appeal (26.1%), while some emphasised representation (17.6%) and entertainment or escapism (9.2%). However, discontinuation was often driven by religious and moral values (61.2%) and dissatisfaction with repetitive storylines (28.6%). The findings reveal a nuanced engagement with these genres, reflecting both their appeal as platforms for identity exploration and the challenges posed by deeply ingrained cultural and religious norms. While Yaoi and Yuri media foster empathy and cultural dialogue, their broader acceptance remains constrained by societal values. The study underscores the need for culturally sensitive storytelling that aligns with local traditions and universal themes to promote inclusivity without undermining societal norms. These findings contribute to understanding the dynamics of globalised media consumption in conservative societies, offering insights into the interplay between global narratives and local cultural frameworks.